Transition processes in Lithuania and other east – and Central European countries: Development of university and professional studies system - Melnikas, Borisas (Journal of Business Economics and Management, 2004)
The present state of university and professional education in Lithuania and major problems of its development are outlined. The possibilities of upgrading university and professional studies are evaluated, taking into account the processes associated with the integration of Lithuania into the European Union. In addition, the prospects of education development are analyzed in the context of transitions characteristic of the states of Central and Eastern Europe.First Published Online: 14 Oct 2010